The Fulfillment Center Intervention Study: Protocol for a group-randomized control trial of a participatory workplace intervention - Erin L. Kelly; Kirsten F. Siebach; Grace DeHorn; Megan Lovejoy (PLOS ONE, 2024)
Warehousing and storage is an economically vital industry, with 1.2 million workers in 2020. The Fulfillment Center Intervention Study focuses on workers in fulfillment centers in the e-commerce segment of this industry. Fulfillment centers are a growing yet understudied work environment which provides a unique setting to further examine how working conditions and worker voice influence health. The Study involves a group-randomized controlled trial comparing participants in worksites randomized to launch the participatory intervention (Health and Well-Being Committees, or HaWCs) with participants working for the same firm in control sites. HaWCs serve as a new formal voice channel where a small group of frontline workers and supervisors solicit workers' concerns and ideas about safety (e.g., physical hazards), the psychosocial environment (e.g., how workers feel about their treatment at work), and work organization (e.g., workflow, training opportunities, scheduling) and then develop and implement improvement projects in response. The primary objectives of the study are to evaluate the efficacy of the HaWC intervention and its effect on mental health outcomes and changes in the conditions of work within fulfillment centers, and to conduct a process evaluation of key contextual factors that support effective intervention implementation and sustained engagement. To our knowledge, this will be the first trial of a participatory intervention within a fulfillment center setting. Anticipated challenges include competing demands and company initiatives that may limit management support and high turnover. Should the intervention be shown to be feasible, the outcomes from this study will inform future randomized controlled trials of participatory interventions. Trial registration: This trial is registered with the ClinicalTrials.gov registry ( NCT05199415 ) and approved by the Institutional Review Board (IRB) at the Massachusetts Institute of Technology (Protocol: 200800024).
Keywords: 300